2022
DOI: 10.1073/pnas.2204172119
|View full text |Cite
|
Sign up to set email alerts
|

The structure of prior knowledge enhances memory in experts by reducing interference

Abstract: The influence of prior knowledge on memory is ubiquitous, making the specific mechanisms of this relationship difficult to disentangle. Here, we show that expert knowledge produces a fundamental shift in the way that interitem similarity (i.e., the perceived resemblance between items in a set) biases episodic recognition. Within a group of expert birdwatchers and matched controls, we characterized the psychological similarity space for a set of well-known local species and a set of less familiar, nonlocal spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…As noted above, there are bidirectional connections between the vmPFC and hippocampus that are critical for mental simulation, and these pathways activate important subcortical areas relevant for the appraisal aspect of the simulation, including the amygdala that supports emotional appraisals (Bechara & Damasio, 2005; Rangel et al, 2008). Critically, the nature of the interaction between the vmPFC and the hippocampus during mental simulation—and the activity of these intervening regions—is thought to depend on the content included in the simulation (Greve et al, 2019; Ritchey & Cooper, 2020; Sheldon et al, 2019; van Kesteren et al, 2012; Wing et al, 2022).…”
Section: Autobiographical Memory and The Neural Basis Of Schema-congr...mentioning
confidence: 99%
“…As noted above, there are bidirectional connections between the vmPFC and hippocampus that are critical for mental simulation, and these pathways activate important subcortical areas relevant for the appraisal aspect of the simulation, including the amygdala that supports emotional appraisals (Bechara & Damasio, 2005; Rangel et al, 2008). Critically, the nature of the interaction between the vmPFC and the hippocampus during mental simulation—and the activity of these intervening regions—is thought to depend on the content included in the simulation (Greve et al, 2019; Ritchey & Cooper, 2020; Sheldon et al, 2019; van Kesteren et al, 2012; Wing et al, 2022).…”
Section: Autobiographical Memory and The Neural Basis Of Schema-congr...mentioning
confidence: 99%
“…Strategic policies around landscape involve experts communicating their knowledge to people with different backgrounds, but expert conceptual representations may differ from lay people in important ways. Previous studies in other domains, such as folk biology, have shown that experts have more alternative knowledge structures to draw upon when making judgments about the structure of a domain (Boster & Johnson, 1989; Wing, Burles, Ryan, & Gilboa, 2022). For example, rather than relying primarily on surface‐level perceptual features, experts also use functional information to make judgments.…”
Section: Introductionmentioning
confidence: 99%
“…Neuroimaging experiments have demonstrated shared neural activation 5 and functional connectivity 6,7 during episodic and semantic memory processes, and preexisting semantic knowledge can act as a scaffold to facilitate the acquisition of new episodic memories [8][9][10] . Moreover, semantic relatedness can help facilitate memory in the face of increased interference [11][12][13] and promote integration of to-be-learned materials to later improve memory [14][15][16] . Conversely, episodic learning can selectively reshape pre-existing semantic information, for instance by increasing discriminability of within-category items by expanding representations of to-be-learned information and minimizing those of irrelevant information 17,18 .…”
Section: Introductionmentioning
confidence: 99%